Intraluminal obstruction of the proximal duodenum in two animals of the genus Ateles spp - Case report (Research, Society and Development, 2023)
Intestinal obstruction in non-human primates by a foreign body of fruit origin is uncommon in the surgical clinical routine of wild animals, but it is relevant when it comes to rescued animals that have undergone dietary changes, which can lead to erroneous ingestion of whole fruits and seeds of great size. Thus, this case relate aims to report two animals of the genus Ateles spp. presenting acute abdominal discomfort which underwent to exploratory celiotomy observing an intraluminal obstruction by a foreign body of fruitful origin. In both cases the animals underwent to surgical treatment and postoperative management. Clinical improvement was observed in both animals and it was possible to return them to the rescue centers. It was concluded that the diagnosis, treatment and postoperative management was efficient for maintaining the lives of these primates.